2016
DOI: 10.1111/j.1755-3768.2016.0613
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and reversal of selenite‐induced cataracts by N‐acetylcysteine amide in Wistar rats

Abstract: Background: The present study sought to evaluate the efficacy of N-acetylcysteine amide (NACA) eye drops in reversing the cataract formation induced by sodium selenite in male Wistar rat pups. Methods: Forty male Wistar rat pups were randomly divided into a control group, an N-acetylcysteine amide-only group, a sodium selenite-induced cataract group, and a NACA-treated sodium selenite-induced cataract group. Sodium selenite was injected intraperitoneally on postpartum day 10, whereas N-acetylcysteine amide was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Thus, much emphasis is being laid on identification of compounds that will help to prevent cataractogenesis in the first place. Natural and synthetic compounds have been shown to prevent cataract formation induced by selenite and other chemicals [39][40][41]. In these studies aimed at the developmental stages of cataract, there is a strong scientific basis for therapy using antioxidant and anti-inflammatory properties of specific compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, much emphasis is being laid on identification of compounds that will help to prevent cataractogenesis in the first place. Natural and synthetic compounds have been shown to prevent cataract formation induced by selenite and other chemicals [39][40][41]. In these studies aimed at the developmental stages of cataract, there is a strong scientific basis for therapy using antioxidant and anti-inflammatory properties of specific compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It has demonstrated efficacy in numerous in vitro and animal models of other oxidative stress-related conditions, including drug-induced RPE damage and cataracts. [11][12][13][14][15] Our lab has demonstrated that NACA prevented retinal degeneration in vitro and in animal models.14 The immortalized ARPE-19 cell line was used as an in vitro model because primary human RPE cells were not available at the time. ROS generation and lipid peroxidation induced by tert-butyl hydroperoxide (TBHP) were reversed by pretreatment with NACA.…”
mentioning
confidence: 99%